Could time-intensity by a trained panel be replaced with a progressive profile done by consumers? A case on chewing-gum - Galmarini, Mara Virginia (2015)
Fil: Galmarini, Mara Virginia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina